Two Cultures into One?. (15th February 2018) - Blockmans, Wim
Abstract : Over the last few decades, two developments have brought fundamental changes to the study of the humanities. The digital revolution triggered the construction of huge databases, universally accessible and searchable on an unprecedented scale. As a consequence, new ways of thinking in wider contexts and organizing research on a larger scale came within reach of disciplines that had previously mostly been active on an individual level and focusing on particular phenomena. Moreover, applications of new scientific methods led to breakthroughs in fundamental humanities issues such as environmental and biological data that were essential for living conditions and for the formation of collective identities. The increased collaboration between disciplines led to major innovations.